Mass participation in art : patterns and unpredictability - Ferreira, Luís Manuel de Sousa Sarmento (2018)
A work of art's openness to participation is traditionally a focus for thought and debate on the artists’ role and on the way the participants relate to the artistic process. A recent artistic development in participation art - a formal definition of a work that involves a massive number of participants – calls for a reassessment of participation strategies and the study of the effects of this change on practices where the involvement of the other is simultaneously a method of art making and a field of poetic potential. In this thesis, current theoretical work on the broader context of participation has been critical to define mass participation within that field. However, a shift from views centred on the new status of the participant public and its impact on the social and political context of the artwork towards a view centred on the artists’ options is needed to assess the particularities of this practice. This shift reflects our research position that mass participation follows a process of artists’ gradual ceding of authorial control to external elements. This process, that we will argue to have its roots in ancient art, is further explored by the vanguards of the early twentieth century, and is part of current art practice and discourse. Such timeline has already been clearly described elsewhere. However, the distinctive trait of mass participation, in what relates to that agency transfer is a set of form making strategies which have lately come together even if they have been individually sought throughout modern and contemporary artistic endeavour. As such, the work here documented, involves the systematization of such strategies resorting to two main approaches: on one hand, through practice, dealing with the formal and poetical potential of working with the mass. The main conceptual and implementation themes of four projects, that are accounted for in the second half of this document, establishes the seeds for the proposition of a mass participation strategy; on the other hand, a theoretical generalization effort, that makes for the first half of this document, creates the abstract framework of such proposition. Along with its general technological, cultural and artistic context, mass participation is posited within a critical review of the notions of agency, participation, the mass, and complexity.